Effectiveness of theory-based breast self-examination intervention for breast cancer prevention among female college teachers in Pakistan: A cluster randomized controlled trial study protocol - Benazir Mahar; Malina Binti Osman; Fatimah Binti Ahmad Fauzi (PLoS ONE, 2025)
Background Breast cancer poses a significant health challenge in Pakistan, with a disproportionately high number of cases diagnosed at advanced stages. Despite the rising incidence, preventative measures like regular screening remain not commonly practiced among Pakistani women. While extensive research exists on breast cancer globally, there is a critical gap in studies specifically designed and evaluated to enhance breast self-examination practices within the Pakistani context. Methodology The primary goal of this study is to design and implement an educational intervention on breast self-examination and evaluate its effectiveness among college teachers in Pakistan. This protocol outlines a single-blind, parallel cluster randomized controlled trial (CRCT) with an intervention period of three months. Clusters will be randomly assigned to either the control or intervention groups,and baseline data will be gathered from both groups. An intervention based on the health belief model will be executed for the intervention group to improve women’s knowledge and behaviors about breast self-examination (BSE). Data will be collected at two follow-up intervals for both groups post-intervention. The modified questionnaires include constructs such as breast cancer symptoms, risk factors, detection techniques, frequency and practices of breast self-examination, and perceptions of breast cancer. The control group will get the intervention once the trial concludes. The primary outcome of this study is breast self-examination (BSE) practice, whereas secondary outcomes encompass knowledge and beliefs related to breast cancer and BSE. Discussion This cluster randomized controlled trial is aimed to improve the efficacy and legitimacy of theory-based intervention by increasing women’s knowledge of breast self-examination and breast cancer and changing their attitudes to encourage early breast cancer detection by practicing breast self-examination. This might significantly allow an improved detection rate; therefore, earlier treatment can be offered. Therefore, lower the death rate from breast cancer and guide health promotion initiatives in other comparable settings. Furthermore, less aggressive therapies are frequently possible with early detection, which enhances healthcare cost-effectiveness while also improving patient outcomes and treatment burdens. Trial registration This study protocol is registered with the Thai Clinical Trial Registry (TCTR), TCTR20240703005 (https://www.thaiclinicaltrials.org/show/TCTR20240703005). The following study protocol complied with the Standard Protocol Items Recommendations for Interventional Trials (SPIRIT) checklist. (S1 file).